WHAT CONTRIBUTES TO BETTER OVERALL EVALUATIONS WHEN APPLYING FOR A JOB? SOCIABILITY OR COMPETENCE? THE ROLES OF TRAIT AND WORK SETTING IN GAINING POSITIVE OVERALL EVALUATIONS - Jijyan, Hovhannes (Modern Psychology, 2024)
Job candidate evaluation is relevant for any organization, however the factors which lead to positive evaluations have been argued upon by researchers, mainly stating their differing opinions on the context of the job and the climate of the organization. This paper investigates whether trait and setting have an impact on candidate evaluation, and if they do, which factor has the most influence. The study used a 2x2 experimental between-subjects design, with overall evaluation as the measured variable. Trait was measured through sociability and competence. Setting was defined as either working from home or at the company office. The hypotheses of the paper were the following; Candidates scoring higher on sociability will receive more positive overall evaluations, this relationship will be stronger for those candidates who are expected to work physically from the office. 267 participants completed a questionnaire assessing their decision in hiring a candidate who is high in sociability or competence, while also including the job setting as an influencing factor in this model. After analyzing the data, it was found that sociability does in fact lead to more positive overall evaluations. The results led to the conclusion, that the candidate who was more sociable rather than competent was chosen by raters. Setting did not have a significant interaction effect with trait, concluding that working remotely, or at the company office does not affect the respondent’s choice on preferring sociability over competence in a potential candidate.